SISTEM INFORMASI MANAJEMEN AKADEMIK DAN KOMPETENSI GURU UNTUK MENINGKATKAN MUTU HASIL PEMBELAJARAN - Nada Shofa (stit-islamic-village, 2019)
Quality of learning outcomes in high school Islamic Village Tangerang has not led to the skills performed by the teacher and the guidance values, resulting in a negative image and persuasive in students as well as cause disappointment for every customer education, it arose because of inadequate teachers to master how to put together a lesson plan which arranges content, media technology, and value in every learning process. Formulation of the problem in this research are as follows: 1) how the academic management information systems influence against the quality of learning outcomes?, 2) how the influence of teacher competence against the quality of learning outcomes?, 3) How the influence of the system information management competency and academic teachers together against quality learning outcomes?. This research was carried out by using the eksplanatori method of non-experimental. The population in this study was the HIGH SCHOOL teachers in Islamic Village Tangerang as many as 38 people. The technique of sampling in the census.The results showed a positive effect management information systems against the quality of the learning outcomes of 45.5% with P value 0.000 or α < 0,05. Influential teacher competence positively against the quality of the learning outcomes of 62.6% with P value 0.000 or α < 0,05. Management information system of teacher competence and positive effect toward the quality of the learning outcomes of 69.7% with P value 0.000 or α < 0,05